2010
DOI: 10.2337/db10-0004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on the Relationships of Brown Adipose Tissue With Sex and Adiposity in Humans

Abstract: OBJECTIVEBrown adipose tissue (BAT) regulates energy homeostasis and fat mass in mammals and newborns and, most likely, in adult humans. Because BAT activity and BAT mass decline with age in humans, the impact of BAT on adiposity may decrease with aging. In the present study we addressed this hypothesis and further investigated the effect of age on the sex differences in BAT activity and BAT mass.RESEARCH DESIGN AND METHODSData from 260 subjects (98 with BAT and 162 study date–matched control subjects) who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
287
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(311 citation statements)
references
References 21 publications
18
287
5
1
Order By: Relevance
“…A significant decrease in thermogenesis in BAT and browning of WAT has been described as a result of increased age in humans and rodents (Florez‐Duquet, Horwitz, & McDonald, 1998; Pfannenberg et al, 2010; Yoneshiro et al, 2011). We therefore examined the effects of cold exposure in Postn ‐knockout mice and observed a rapid loss of body weight within 72 hr of cold exposure which prevented further long‐term treatments (Figure 3a,b).…”
Section: Resultsmentioning
confidence: 99%
“…A significant decrease in thermogenesis in BAT and browning of WAT has been described as a result of increased age in humans and rodents (Florez‐Duquet, Horwitz, & McDonald, 1998; Pfannenberg et al, 2010; Yoneshiro et al, 2011). We therefore examined the effects of cold exposure in Postn ‐knockout mice and observed a rapid loss of body weight within 72 hr of cold exposure which prevented further long‐term treatments (Figure 3a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, agerelated decline in BAT activity was also demonstrated. 1,5,26 Our subjects were young and almost all were lean; therefore, the impact of UCP1 gene polymorphism on REE may be greater than that in other age groups. Long-term study is needed to investigate the impact of the G allele of the UCP1 gene on future weight gain in females around menopause; 27 moreover, studies including male subjects of various ages are required.…”
Section: Limitationsmentioning
confidence: 99%
“…Multiple recent studies have shown that adult humans have functional BAT that can be activated in response to cold exposure in a process called nonshivering thermogenesis (1)(2)(3)(4). In both small and large population studies (1,2,4,5), there is an inverse correlation between BAT activity and obesity, suggesting that activating BAT, through pharmacological, environmental, or potentially nutritional interventions, could become a therapeutic means to treat obesity and diabetes. Indeed, human BAT energy expenditure may be a critical counterbalance to the weight gain and metabolic dysregulation caused by excess energy storage in white adipose tissue.…”
mentioning
confidence: 99%